Therapeutic Doll Interventions for People Living with Dementia in Care Homes: A Scoping Review - Elizabeth Henderson; Hannah McConnell; Gary Mitchell (Nursing Reports)
Doll therapy is a psychosocial intervention that has been commonly used within dementia care for many decades. The practice of doll therapy involves supporting people with dementia to engage with a therapeutic doll and this has been associated with positive changes in a person’s wellbeing and behavior. While there have been several systematic reviews that have focused on behavioral outcomes, limited reviews have explored the broader psychosocial outcomes associated with doll therapy in care home settings. A scoping review of the literature was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews (PRISMA-ScR). Four electronic databases were searched systematically (CINAHL Plus, Medline, PsycINFO, and PubMed). Twelve primary research studies from the past ten years (2013–2023) were included in this review. Primary data were synthesized using a narrative synthesis methodology. The three main themes from this review relate to a reduction in levels of behavioral and psychological symptoms of dementia (BPSD), increased communication skills, and a reduction in caregiver distress. Doll therapy has the potential to be an effective person-centered intervention that can enhance quality of life for people living with dementia in care home settings.